The problem of combustion instability in liquid rocket engines - Samir Vekilov; Volodymyr Lipovskyi; Roman Pustovyi (Challenges and Issues of Modern Science)
The purpose of this work is to carry out an overview on combustion instability in liquid propellant rocket engines, its classification, the main principles of occurrence as well as ways to prevent the phenomena while designing of the prospective engine. A new approach is based on maximum utilization of the additive technologies for production of the liquid propellant rocket engines. In the work the actual state of the problem of combustion instability is shown through retrospective overview of the phenomena occurrence during development of the know rocket engines. The actuality of the problem is emphasized by presenting some of the results obtained by authors while developing a prospective rocket engine. Particularly, in the following work the results of the development of the low-thrust rocket engine with the use of L-PBF additive technology is considered. While development the specimens experienced extremely low-frequency instability of 1 Hz. Further, in the process of searching for the reasons of the phenomena occurrence, the theoretical knowledge available in the literature was structured and presented in the work. The formed knowledge on the subject of combustion instability phenomena became useful while finding the reason of occurrence of 1 Hz frequency in the developed engine chamber. It was determined that the surface roughness typical for L-PBF process is the main contributor to the issue. Thus, a complex of modifications was applied to the chamber in order to prevent combustion instability in the developed low-thrust rocket engines. The presented data forms basis for the further development of the design recommendation and effective methodology for designing prospective rocket engines manufactured with the use of additive technologies. The paper bears a review type with the empirical data representation.